Development and characterization of multifunctional PassDop layers for local p+-laser doping. (September 2017) - Norouzi, Mohammad H.; Saint-Cast, Pierre; Lohmüller, Elmar; Steinhauser, Bernd; Benick, Jan; Werner, Sabrina; Bitnar, Bernd; Palinginis, Phedon; Neuhaus, Holger; Hofmann, Marc; Wolf, Andreas
Abstract: We present the development of aluminum oxide (AlOx ) and boron-doped silicon nitride (SiNx :B) layer stacks for application on the back side of monocrystalline p-type silicon wafers. Two deposition techniques are used for the deposition of the AlOx /SiNx :B layer stacks, atomic layer deposition and plasma-enhanced chemical vapor deposition. Both techniques enable excellent surface passivation with surface recombination velocities of 4 cm/s after firing. Also, heavy local doping with sheet resistances down to 20 Ω/sq is possible by laser processing. We call this concept the PassDop approach. For the laser processed area where the silicon surface is locally boron-doped and the AlOx /SiNx :B passivation layer stack is locally removed, a quite low dark saturation current density of about 900 fA/cm 2 is determined. The PassDop approach can be a solution to realize passivated emitter and rear locally doped PERL solar cells by improving their rear side properties while maintaining industrial applicability.